Drug-related cardiac pathology. Issue 12 (27th November 2009) - Butany, J; Ahn, E; Luk, A
Abstract : Many commonly used drugs, with each causing changes that may be potentially lethal, can adversely affect the function of the heart. In addition some drugs have synergistic effects that can also damage cardiovascular tissues. The drug-related cardiotoxic effects of antineoplastic agents, psychotropic medications, heavy metals, substances of abuse, promotility agents, antihistamines, antimicrobials and antiarrhythmic agents are discussed. Hypersensitivity myocarditis is also discussed.